Potential of ginger (Zingiber Officinale) crude extract as a chemotherapeutic agent for nile tilapia (Oreochromis Niloticus) infected by achlya sp. / Norashikin Anjur and Ruzaini Ahmad - Anjur, Norashikin; Ahmad, Ruzaini (UiTM Cawangan Negeri Sembilan, 2022)
The outbreaks of Achlya sp. have resulted in enormous mortality of cultured fish and remain a critical disease problem, resulting in significant losses in aquaculture productivity. Experimental infection of Nile tilapia (Oreochromis niloticus) juvenile by Achlya sp. was conducted to examine the potential of ginger crude extract as a chemotherapeutic agent. A total of 100 juveniles were immersed in four different concentrations of crude ginger extract at 100 ppm, 500 ppm, 800 ppm and 1000 ppm while 0 ppm as the control treatment. The potential of the extract as a treatment agent in the infected fish was recorded in terms of fish survival rate and changes in physical appearance. The results show that the treated fish immersed in a lower concentration of ginger extract (100 ppm, 500 ppm and 800 ppm) possess a higher survival rate and no Achlya sp. found on the fish skin compared to the non-treated control. The highest concentration of ginger extract at 1000 ppm might be toxic to the fish due to a lower survival rate compared to other treatments. It shows that ginger crude extract potentially acts as a chemotherapeutic agent for fungal infection in tilapia juveniles when used in the appropriate concentration and treatment period.